Didactic Opportunities of Developing the Pedagogical Professional Competence of Students of Higher Education Institutions - Imomaliyevna, Yuldasheva Feruza (European Journal of Life Safety and Stability (2660-9630), 2022)
At the heart of any educational system lies the future generation and the interests of the people. Personal qualities of the young generation play a leading role in realizing these interests. The quality of the young generation and the level of professional knowledge are directly related to the type, volume and quality of education that is being given to them today.